2020
DOI: 10.3390/bios10030022
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Nanoparticles Based Sensor for Cocaine Detection

Abstract: The development of a sensor based on molecularly imprinted polymer nanoparticles (nanoMIPs) and electrochemical impedance spectroscopy (EIS) for the detection of trace levels of cocaine is described in this paper. NanoMIPs for cocaine detection, synthesized using a solid phase, were applied as the sensing element. The nanoMIPs were first characterized by Transmission Electron Microscopy (TEM) and Dynamic Light Scattering and found to be ~148.35 ± 24.69 nm in size, using TEM. The nanoMIPs were then covalently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…As the last preparation step, 8.0 μL of 0.1 mg/mL BSA dissolved in 0.1 M PBS containing a 0.1 M KCl solution was placed onto the working electrode surface to block the unwanted active area. 45 The binder and antibody functionalization steps and different EDC:NHS and anti-SARS-CoV-2 S1 antibody concentrations were initially optimized prior to the sensing experiments. Finally, different concentrations of SARS-CoV-2 spike protein were tested to observe the antibody–analyte interaction.…”
Section: Methodsmentioning
confidence: 99%
“…As the last preparation step, 8.0 μL of 0.1 mg/mL BSA dissolved in 0.1 M PBS containing a 0.1 M KCl solution was placed onto the working electrode surface to block the unwanted active area. 45 The binder and antibody functionalization steps and different EDC:NHS and anti-SARS-CoV-2 S1 antibody concentrations were initially optimized prior to the sensing experiments. Finally, different concentrations of SARS-CoV-2 spike protein were tested to observe the antibody–analyte interaction.…”
Section: Methodsmentioning
confidence: 99%
“…Canfarotta et al, reported on the production of nanoMIPs for vancomycin, which were used as antibody-replacements in an ELISA-like format [ 247 ]. MIP Diagnostics’ nanoMIPs were also integrated into gold screen-printed electrodes for the impedimetric detection of cocaine at trace levels [ 248 ]. A simpler and more universal approach to label-free detection of analytes, independent of their electrochemical properties, might be the addition of monomers modified with a redox probe, such as done by Mazzotta et al who used vinyl ferrocene and ferrocenyl methacrylate to detect vancomycin [ 249 ].…”
Section: Commercial Mip Synthesismentioning
confidence: 99%
“…The LOD was 7.90 × 10 –10 mol·L −1 , which is a value comparable to other published methods for diazinon determination. A sensitive nanoMIP electrochemical impedance spectroscopy (EIS) sensor to determine cocaine in environmental samples was presented [ 79 ]. A scheme of the steps involved in the fabrication of the sensor is depicted in Scheme 3 .…”
Section: Analytical Applications Of Mip Nanoparticlesmentioning
confidence: 99%